ETO, a Target of t(8;21) in Acute Leukemia, Interacts with the N-CoR and mSin3 Corepressors - Lutterbach, Bart (American Society for Microbiology, 1998)
t(8;21) is one of the most frequent translocations associated with acute myeloid leukemia. It produces a chimeric protein, acute myeloid leukemia-1 (AML-1)–eight-twenty-one (ETO), that contains the amino-terminal DNA binding domain of the AML-1 transcriptional regulator fused to nearly all of ETO. Here we demonstrate that ETO interacts with the nuclear receptor corepressor N-CoR, the mSin3 corepressors, and histone deacetylases. Endogenous ETO also cosediments on sucrose gradients with mSin3A, N-CoR, and histone deacetylases, suggesting that it is a component of one or more corepressor complexes. Deletion mutagenesis indicates that ETO interacts with mSin3A independently of its association with N-CoR. Single amino acid mutations that impair the ability of ETO to interact with the central portion of N-CoR affect the ability of the t(8;21) fusion protein to repress transcription. Finally, AML-1/ETO associates with histone deacetylase activity and a histone deacetylase inhibitor impairs the ability of the fusion protein to repress transcription. Thus, t(8;21) fuses a component of a corepressor complex to AML-1 to repress transcription.